Control of circadian rhythm on cortical excitability and synaptic plasticity - Lodovichi, Claudia; Ratto, Gian Michele (Frontiers in Neural Circuits, 2023)
Living organisms navigate through a cyclic world: activity, feeding, social interactions are all organized along the periodic succession of night and day. At the cellular level, periodic activity is controlled by the molecular machinery driving the circadian regulation of cellular homeostasis. This mechanism adapts cell function to the external environment and its crucial importance is underlined by its robustness and redundancy. The cell autonomous clock regulates cell function by the circadian modulation of mTOR, a master controller of protein synthesis. Importantly, mTOR integrates the circadian modulation with synaptic activity and extracellular signals through a complex signaling network that includes the RAS-ERK pathway. The relationship between mTOR and the circadian clock is bidirectional, since mTOR can feedback on the cellular clock to shift the cycle to maintain the alignment with the environmental conditions. The mTOR and ERK pathways are crucial determinants of synaptic plasticity and function and thus it is not surprising that alterations of the circadian clock cause defective responses to environmental challenges, as witnessed by the bi-directional relationship between brain disorders and impaired circadian regulation. In physiological conditions, the feedback between the intrinsic clock and the mTOR/RAS-ERK pathway suggests a circadian regulation also of synaptic plasticity. Here we will review some recent findings that link the circadian activation of mTOR to changes of the intracellular concentration of Na+, K+ and Cl- leading to changes in neuronal and network excitability.